ACTIVE ENGLISH FOR 3RD GRADE ELEMENTARY SCHOOL: AN ANALYSIS OF ENGLISH TEXTBOOK - Ashrini Syafira Putri; Evi Karlina Ambarwati (STKIP Persada Khatulistiwa Sintang, 2023)
Textbooks is a type of instructional media that has a significant impact on the learning process. However, one of the challenging tasks that English teachers face on a regular basis is choosing an appropriate textbook for English teaching. An investigation is required to obtain a good English textbook. This study focused on the evaluation and analysis of English KTSP textbooks to Elementary schools’ grade III. For evaluation of the textbook, the framework was used to figure out the strengths and weaknesses of the textbook is Regulation of the Minister of Education and Culture No. 8 Year 2016 and Harmer’s (2007). The results have shown accordance and satisfactory from this textbook, it has accurate materials, affordable, contain Indonesian cultural appropriacy, methodology, teachers’ guide and clear instruction. Nonetheless, this book has poor graphics (blury picture) and lack of add on or extras sources material.